Rekayasa Komposit Matrik Aluminium Diperkuat Alumina Dan Bagasse Ash Dengan Metode Metalurgi Serbuk - Al Ghifari , M Ghazi; Somawardi, Somawardi; Rusdi, Ahamad; Sukanto, Sukanto (Jurnal Inovasi Teknologi Terapan, 2024)
In general, brake linings are made using asbestos materials, but brake linings made from asbestos are very dangerous for health. Therefore, it is necessary to develop innovative environmentally friendly materials, one of which is aluminum matrix composite. This research process aims to determine the effect of differences in hot compaction pressure and sintering temperature on the density and hardness properties of recycled aluminium matrix composites reinforced with alumina and bagasse ash. The method used to make composites from aluminum is the powder metallurgy method, which includes preparation processes, powder mixing, compaction, and sintering. Mixing aluminium, alumina powder, and bagasse ash using a horizontal ball mill machine and using process parameters which include Ball Powder Weight Ratio (BPR) parameters of 10:1, the machine rotation speed of 90 rpm, and grinding time of 2 hours. Meanwhile, the hot compaction process uses a two-way pressing method with a hydraulic pump machine that has a pressure reader. The hot compaction process is carried out with a temperature of 500℃ held for 15 minutes and variations in the two-way compaction pressure used namely 5800 Psi, 6000 Psi, and 6400 Psi. Density testing was carried out by referring to Archimedes’ law with the ASTM B962-17 standard. This test resulted in good results at a pressure variation of 6400 Psi. Meanwhile, for hardness testing, the portable Brinell hardness test was used and referred to ASTM E110-14. In this test, the results were good at a pressure variation of 6400 Psi.